Electoral Reform and Trade-Offs in Representation - BECHER, MICHAEL; GONZÁLEZ, IRENE MENÉNDEZ (The American political science review, 2019)
We examine the effect of electoral institutions on two important features of representation that are often studied separately: policy responsiveness and the quality of legislators. Theoretically, we show that while a proportional electoral system is better than a majoritarian one at representing popular preferences in some contexts, this advantage can come at the price of undermining the selection of good politicians. To empirically assess the relevance of this trade-off, we analyze an unusually controlled electoral reform in Switzerland early in the twentieth century. To account for endogeneity, we exploit variation in the intensive margin of the reform, which introduced proportional representation, based on administrative constraints and data on voter preferences. A difference-in-difference analysis finds that higher reform intensity increases the policy congruence between legislators and the electorate and reduces legislative effort. Contemporary evidence from the European Parliament supports this conclusion.